Investigation of the Thermal Degradation Behavior of Coal/Biomass Blends for Kinetics Analysis with Sequential Method Implication - SHOAIB Hafiz Muhammad; QURESHI Tayyab; KHAN Ihtisham; MAHMOOD Hamayoun; IQBAL Tanveer (Architecture, Civil Engineering, Environment)
Pakistan currently has a problem in the energy supply and demand. There is a large gap between supply and demand for electricity. The depletion of fossil fuels and environmental pollution factors also exist. These factors convert the intention to implement co-firing of coal and biomass. Being agricultural land and producing a significant amount of agricultural waste and have a little valuable use of this waste. Keeping in mind for effective use of this agro-waste the pyrolysis behavior of Pakistani local coal (LC), rice husk (RH), and their blends 75LC/25RH wt.%, 50LC/50RH wt.%, 25LC/75RH wt.% were studied using a thermogravimetric analyzer in a nitrogen environment with 10K/min heating rate. A sequential method approach is used to calculate kinetics parameters quickly and accurately. With the assumption of first-order reaction, calculation is performed. The research findings revealed that the addition of rice husk to the blends led to an increase in the activation energy for devolatilization, rising from 22.9 kJ/mol to 45.2 kJ/mol. However, the activation energy for char degradation decreased from 60.4 kJ/mol (100%LC) to 14.2 kJ/mol (100%RH) as the proportion of rice husk in the blends increased. Moreover, the rate of mass degradation also increased with higher amounts of rice husk in the blends. These results suggest that the decrease in char degradation activation energy allows for a reduction in operational temperature, thereby facilitating a reliable co-pyrolysis process. Such a process holds the potential to design a low-cost and effective gasification process, aiding in overcoming the energy challenges.